Sally Haslanger and Gayatri Chakravorty Spivak on the Possibility of Metaphysics of Resistance and its Implications for Postcolonial Feminist Theologizing. (January 2020) - Peracullo, Jeane C.
In Resisting Reality: Social Construction and Social Critique, contemporary feminist philosopher Sally Haslanger claims that the reality of race and gender (both social constructs) is built on unjust social structures and must be resisted. Meanwhile, contemporary social theorist Gayatri Chakravorty Spivak extends the term 'subaltern' to Third World Asian women who were rendered inarticulate by centuries of oppressive masculinist, imperialist, and colonial rule. This article examines how a metaphysics of resistance, culled from philosophy and postcolonial studies, can contribute to expanding postcolonial feminist theologizing.